Time-Kill Assay of 4-Hydroxypanduratin A Isolated from Kaempferia Pandurata Against Foodborne Pathogens - Soerya Dewi Marliyana; Didin Mujahidin; Yana M Syah; Yaya Rukayadi (Universitas Jenderal Soedirman, 2017)
Time–kill assay was performed for 4-hydroxypanduratin A that was isolated from Kaempferia pandurata rizhome against four important foodborne pathogens, namely Bacillus cereus ATCC 21772, Bacillu subtilis ATCC 6633, Staphylococcus aureus ATCC 29737, and Proteus mirabilis ATCC 21100. The methods have been investigated in term of Minimum Inhibitory Concentration (MIC) and killing time curve using methods of Clinical and Laboratory Standards Institute (CLSI) guidelines. The results showed that 4-hydroxypanduratin A rapid acting in killing bacteria as follow: B. cereus : 1×MIC for 4 h, P. mirabilis: 4×MIC for 0.5 h, meanwhile B. subtilis and S. aureus were 1×MIC for 2 h. In conclusion, 4-hydroxypanduratin A showed strong antimicrobial activity against four important foodborne pathogens.